2007
DOI: 10.1007/s11701-007-0032-z
|View full text |Cite
|
Sign up to set email alerts
|

Potassium-titanyl-phosphate laser assisted robotic partial nephrectomy in a porcine model: can robotic assistance optimize the power needed for effective cutting and hemostasis?

Abstract: A potassium-titanyl-phosphate (KTP) laser through robotic endo-wrist instrument has been evaluated as an ablative and hemostatic tool in robotic assisted laparoscopic partial nephrectomy (RALPN). Ten RALPN were performed in five domestic female pigs. The partial nephrectomies were performed with bulldog clamping of the pedicle. Flexible glass fiber carrying 532-nm green light laser was used through a robotic endowrist instrument in two cases. Power usage from 4 to 10 W was tested. The laser probe was explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Kyriazis et al [ 19 ] first reported 2 cases of unblocked thulium laser-assisted robotic PN with no obvious intraoperative or postoperative complications, and the pathological results showed a negative surgical margin. Boris et al [ 22 ] successfully carried out green laser partial zero ischemia nephrectomy in pigs, and the results showed that the green laser effectively stop bleeding within a very short time, with a tissue penetration rate of only 0.8 mm. The GreenLight laser applied in the present study at 532 nm, was preferentially absorbed by oxyhemoglobin (absorption coefficient 102/cm), but not by rinsing (absorption coefficient 104/cm).…”
Section: Discussionmentioning
confidence: 99%
“…Kyriazis et al [ 19 ] first reported 2 cases of unblocked thulium laser-assisted robotic PN with no obvious intraoperative or postoperative complications, and the pathological results showed a negative surgical margin. Boris et al [ 22 ] successfully carried out green laser partial zero ischemia nephrectomy in pigs, and the results showed that the green laser effectively stop bleeding within a very short time, with a tissue penetration rate of only 0.8 mm. The GreenLight laser applied in the present study at 532 nm, was preferentially absorbed by oxyhemoglobin (absorption coefficient 102/cm), but not by rinsing (absorption coefficient 104/cm).…”
Section: Discussionmentioning
confidence: 99%